2005
DOI: 10.1381/0960892053576677
|View full text |Cite
|
Sign up to set email alerts
|

One-Anastomosis Gastric Bypass by Laparoscopy: Results of the First 209 Patients

Abstract: OAGB is a simple, safe and effective operation with less perioperative risk than conventional gastric bypass, quicker return to normal activities, and better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
99
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 9 publications
3
99
0
3
Order By: Relevance
“…In 2001, Rutledge published the first series of LMGB, a new technique supposed to be equally effective yet easier to perform than LRYGB. Many series followed [5], by minilaparotomy [6] or by laparoscopynotably a 2005 prospective randomized controlled trial [7]-confirming these good results [8]. Despite all that, LMGB is far from gaining general consensus so, what's wrong with LMGB?…”
Section: Discussionmentioning
confidence: 95%
“…In 2001, Rutledge published the first series of LMGB, a new technique supposed to be equally effective yet easier to perform than LRYGB. Many series followed [5], by minilaparotomy [6] or by laparoscopynotably a 2005 prospective randomized controlled trial [7]-confirming these good results [8]. Despite all that, LMGB is far from gaining general consensus so, what's wrong with LMGB?…”
Section: Discussionmentioning
confidence: 95%
“…The differences between the various sealants are largely dependent on the quality and quantity of the two basic components, as well as the nature of the fibrinolysis inhibitor [2,7,18]. For this study, Tissucol Ò /Tisseel Ò fibrin sealant was chosen due to its favorable safety profile (no side effects, no transmitted infectious diseases and no embolization or coagulopathy reported [2,7,8,19,20]), wide-scale use, long clinical history, reported use in laparoscopic procedures [21][22][23] and easy-to-use laparoscopic delivery devices.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent studies have reported the use of fibrin sealants to prevent anastomotic leaks following open gastric bypass [9,20], and laparoscopic bariatric surgery [21][22][23]. These nonrandomized clinical trials suggested that the use of fibrin sealant following surgery in high-risk morbidly obese patients may help reduce early complications, and may prove a useful tool during the learning curve for these complex procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The laparoscopic mini-gastric bypass (LMGB), also known as the one-anastomosis or omega-loop gastric bypass, was devised 16 years ago by Dr. Robert Rutledge [11,12] and has been adopted progressively by bariatric surgeons [13][14][15][16][17][18][19][20][21][22], as a safe, rapid and effective procedure. After performing various bariatric operations, the author was trained in the LMGBP by Dr. Rutledge and has been conferring with the other LMGBP surgeons worldwide, especially at the annual Paris LMGB Consensus Conferences.…”
mentioning
confidence: 99%